Realistic simulation: satisfaction and self-confidence of nursing students - Breno Monteiro Mota; Joyce Oliveira Alarcon Nakamura; Taiane Lucena Cavalcante; Fabiane dos Santos Ramos; Samanta Oliveira da Silva Diniz (Revista Enfermagem Digital Cuidado e Promoção da Saúde)
OBJECTIVE: To evaluate nursing students’ satisfaction and self-confidence regarding simulation as an active teaching methodology. METHOD: A descriptive study developed with 96 students from the 8th, 9th and 10th periods of the nursing undergraduate course at a private University in the state of Rio de Janeiro in August and September 2021. The Scale “Student Satisfaction and Self-Confidence in Learning” was applied to measure the satisfaction and self-confidence of students obtained through simulation. RESULTS: Students were equally satisfied (mean= 4.5) and self-confident (mean= 4.5) with the simulation. CONCLUSION: The study showed that simulation promotes a high level of satisfaction with learning and self-confidence with the skills acquired, reinforcing the potential of simulation as a teaching and learning strategy.